The nexus between cocoa production and deforestation - Asare, R. (2019)
In Ghana, cocoa contributes substantially to the agricultural foreign earnings and plays a major role in providing income for millions of farmers and households. But its production has environmental impacts, like deforestation. Creating a policy environment that supports sustainable practices in agriculture to leverage the cocoa forests for biodiversity conservation is essential.